Therapeutic exercise and orthopedic manual therapy for impingement syndrome: A systematic review - Desmeules, F.; Cote, C. H.; Fremont, P. (Clinical Journal of Sport Medicine, 2003)
Objective: To review randomized controlled trials evaluating the effectiveness of therapeutic exercise and orthopedic manual therapy for the treatment of impingement syndrome. Data Source: Reports up to October 2002 were located from MEDLINE, the Cochrane Database of Systematic Reviews, the Physiotherapy Evidence Database (PEDro), the TRIP database, and the Cumulative Index to Nursing & Allied Health Literature (CINAHL) using "shoulder" and "clinical trial"/"randomized controlled trial" as search terms. Study Selection: Studies were included if (1) they were a randomized controlled trial; (2) they were related to impingement syndrome, rotator cuff tendinitis, or bursitis; (3) one of the treatments included therapeutic exercise or manual therapy. Data Extraction: Two independent observers reviewed the methodological quality of the studies using an assessment tool developed by the Cochrane Musculoskeletal Injuries Group. Differences were resolved by consensus. Data Synthesis: Seven trials met our inclusion criteria. After consensus, the mean methodological score for all studies was 13.9 ± 2.4 (of 24). Four studies of 7, including the 3 trials with the best methodological score (67%), suggested some benefit of therapeutic exercise or manual therapy compared with other treatments such as acromioplasty, placebo, or no intervention. Conclusions: There is limited evidence to support the efficacy of therapeutic exercise and manual therapy to treat impingement syndrome. More methodologically sound studies are needed to further evaluate these interventions.